IMPLICIT THEORIES OF INTELLIGENCE: THE IMPACT OF INCREMENTAL MINDSET INTERVENTION ON STUDENT’S ACHIEVEMENT GOALS - Tahereh Mehrollahi; Mariani Md Nor; Mahmoud Danaee (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The achievement goal approach has led to educational and social- psychology as a foundation of practical education in schools. The implicit theory of intelligence, which is one of the leading models in motivation, is deep-rooted in goal theory. This theory suggests the student’s belief system is divided into an entity and incremental mindset, which links each with a specific goal orientation: learning, performance, learning avoidance, and performance-avoidance. Therefore, the implicit theory of intelligence is considered an antecedent of achievement goals, which means that by changing the student’s mindset, their goals and achievement levels will also change. This study investigates the effect of an incremental mindset intervention on student’s achievement goals through a quasi-experimental design. For this purpose, a population of fifty-five eighth-grade female students was classified into control and experimental groups. Both groups performed the pre-, post-, and follow-up tests of goal orientations. The two-way repeated measures of MANOVA results showed a statistically significant difference in the impact of the applied intervention on student’s goal orientation between the tested groups against time (F=5.585, P<0.001, Î·2=0.100).